A escala centiloide na avaliação e classificação Β-Amiloide em diferentes trajetórias cognitivas do envelhecimento - Souza, Giordana Salvi de (2021)
Aging has its effects at the molecular, cellular, vascular, and morphological level and brain aging can follow as a successful aging (superagers), a normal aging and a pathological aging (Alzheimer's disease). Pathological aging presents the as the extracellular accumulation of senile plaques composed of the β-amyloid peptide (βA) and tau protein. Imaging techniques using positron emission tomog-raphy or PET have provided new approaches to support a differential diagnosis of dementia. The Centiloid (CL) scale was developed to reduce processing pro-tocol variability and produce a more accurate and harmonized quantification of PET images acquired with different βA radiotracers. This study aims to explore the use of the CL scale in PET quantification with βA radiotracers to assess dis-tinct cognitive aging trajectories by investigating the βA classification of individu-als using different cutoff points for βA positivity. The CL scale conversion equa-tion was applied to four groups: superagers (SA), healthy age-matched controls (AC), healthy middle-aged controls (MC), and Alzheimer's disease (AD). Three different cut-off points of βA burden positivity (Jack et al. 2017, Salvadó et al. 2019, and Amadoru et al. 2020) were applied to CL scale values to differentiate early pathophysiological βA accumulation and established pathological βA. The DA group exhibited significantly increased βA load compared to MC, but not AC. Both groups of healthy controls were not significantly different from each other. Depending on the cut-off point used (10 CL, 19 CL, or 30 CL), 7.5% of our sub-jects were misclassified into βA positivity and three SA subjects were classified as βA positive. For the AC group, we obtained about 40 to 60% of individuals classified as positive. Although the CL scale was developed to standardize the method of image acquisition and processing, a study is still needed to standardize the cut-off points for differentiating individuals along the CL values. The results of this study confirm the International Working Group (2021) recommendations, that the diagnosis of AD should consider biological patterns and clinical symptoms, and preclinical assessment of βA positivity is not recommended.